Analizando la relación entre la eficiencia y la rentabilidad en el mercado de seguros no vida; Studying the relation between efficiency and profitability in the non-life insurance market - Sara Suárez Fernández; Raquel Quiroga García; Isabel Manzano Pérez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– Previous literature on business performance in the insurance market tends to focus only on efficiency or profitability. However, the relationship between both has yet to be addressed in the Spanish insurance market. This paper examines the relationship between efficiency scores obtained through a two-stage DEA and the values of the classical financial ratios (ROE, ROA, Technical Ratio, Combined Ratio and Loss Ratio). We use a sample of 111 firms from the non-life Spanish insurance market from 2008-2017. We find a positive relationship between efficiency and profitability, which shows decreasing returns, with the positive effect of efficiency on profit ratios being lower for the most efficient companies.
Keywords: 330; Efficiency; Profitability; Insurance; Data Envelopment Analysis